The Current LHC Limits for the TBESS Lagrangian - Gintner, Mikulas; Juran, Josef (Communications - Scientific letters of the University of Zilina, 2017)
We investigate how the recent LHC measurements limit the parameters of the hypothetical vector resonance triplet. The vector resonances are assumed to represent bound states of hypothetical strongly-interacting new physics, a candidate of the extension of the Standard model.